Respostas

2013-09-02T02:18:18-03:00
1) (-3)^{3}*x*(-2)^{2}+(-3)+5^{0} =
(-27)*x*(4)+(-3)+1 =
(-108)*x-2 =
-108x-2

2) 4-((-2)^{2}*x*(-3)-(-11+(-3):(-4))-(-1)) =

Resolvemos apenas os sinais e o expoente:
4-(4*x*(-3)-(-11+3:4)+1) =

Transformamos -11 em -44:4
4-(-12*x-(-44:4+3:4)+1) =
4-(-12*x-(-41:4)+1) =
4-(-12*x+41:4+1) =
4+12*x-41:4-1 =
16:4+12*x-41:4-4:4 =
12*x-29:4 =

12x-7,25
1 5 1
Pq Se Transforma o -11 em -44:4?
para poder somar com o 3:4
-11 = -11 * 1 = -11 * (4:4) = -44:4
Muito Obrigada.... Ajudou D+..